Brucella Omp25 Upregulates miR-155, miR-21-5p, and miR-23b to Inhibit Interleukin-12 Production via Modulation of Programmed Death-1 Signaling in Human Monocyte/Macrophages - Cui, Beibei; Liu, Wenli; Wang, Xiaoya; Chen, Yu; Du, Qian; Zhao, Xiaomin; Zhang, Hai; Liu, Shan-Lu; Tong, Dewen; Huang, Yong (Frontiers in Immunology, 2017)
Brucella spp. infection results in compromised Type1 (Th1) cellular immune response. Several reports have described an immunomodulatory function for Brucella major outer membrane protein Omp25. However, the mechanism by which Omp25 modulates macrophage dysfunction has not been defined. Herein, we report that Omp25-deficient mutant of B. suis exhibited an enhanced ability to induce interleukin (IL)-12 whereas ectopic expression of Omp25 protein inhibited TLR agonists-induced IL-12 p70 production through suppression of both IL-12 p40 and p35 subunit expression in THP-1 cells. In addition, Omp25 significantly up-regulated miR-155, -23b and -21-5p, as well as the immunomodulator molecule programmed death-1 (PD-1) in monocyte/macrophages. The up-regulation of miR-155 and -23b correlated temporally with decreased TAB2 levels, IκB phosphorylation and IL-12 p40 levels by targeting TAB2 and il12B 3’UTR, respectively, while miR-21-5p increase directly led to the reduction of LPS/R848-induced IL-12 p35 protein by targeting il12A 3’UTR. Consistent with this finding, reduction of miR-155 and -23b attenuated the inhibitory effects of Omp25 on LPS/R848-induced IL-12 p40 expression at both transcriptional and post-transcriptional levels, while reduction of miR-21-5p attenuated the inhibitory effects of Omp25 on LPS/R848-induced IL-12 p35 expression at the post-transcriptional level, together significantly enhanced IL-12 p70 production upon LPS/R848 stimulation. We also found that blocking PD-1 signaling decreased the expression of miR-155, -23b and -21-5p induced by Omp25 and enhanced IL-12 production in monocyte/macrophages. Altogether, these data demonstrate that Brucella Omp25 induces miR-155, -23b and -21-5p to negatively regulate IL-12 production at both transcriptional and post-transcriptional levels via regulation of PD-1 signaling, which provides an entirely new mechanism underlying monocyte/macrophages dysfunction during Brucella spp infection.